Board efficiency, Professional management, Ethics, and Financial Performance of firms in sub-Sahara Africa: Does Size Matter? - Okofo-Dartey, Emmanuel; Bosomtwe, Emmanuel (Acta Universitatis Danubius. Œconomica, 2023)
The study examines the impact of board efficiency, professional management, and ethics on the financial performance of firms in SSA after considering the sizes of these firms. Firm and country-level data for non-finance firms in SSA are obtained from the Bloomberg Terminal from 2007 to 2017. The OLS, Fixed, Random Models, and the difference GMM techniques are used for the analysis. The study results reveal that board efficiency is negatively related to the profits of firms in SSA which is proxied by the ROAs of the firms, but it positively impacts Sales. Professional management also has a positive relationship with profits and negatively relates to Sales, while Ethics also has a negative relationship with Sales, The study further finds that, by considering the sizes of the firms, board efficiency positively affects sales levels of firms in SSA, professional management has a positive impact on the firms' profits while ethics also affect profits of the firms positively. Therefore, this study provides significant implications for firms and gives firms’ management a framework for adoption in managing their business activities.